ENLIGHTENMENT IN THE FINAL AGE: THE SINGLE PRACTICE MOVEMENTS OF HONEN, SHINRAN AND NICHIREN - Meulen, Cindy Vander (My University, 1997)
It is not entirely clear why medieval Japanese Buddhist figures moved away from earlier practices and doctrinal positions which were tolerant of a variety of teachings. Jackie Stone, in her articles "Seeking Enlightenment in the Last Age: Mappo Thought in Kamakura Buddhism Parts I and II" introduces a hypothesis that addresses this very issue. She argues that the idea of the sole validity of a single path to enlightenment in Kamakura times was not only relatively new but also resulted from "mappo consciousness" (an awareness of living in a Degenerate Age) emerging at this point in Japanese Buddhist history. Stone's argument is based on an assumption. She takes for granted that the portrayal of Kamakura times as corrupt by Nichiren and other Buddhist leaders is secular and is not vested with religious interpretations. I shall present the possibility that the religious leaders Stone discusses responded to their own interpretation of events by putting forth a "new" practice and did not necessarily respond to a historical reality in Kamakura times of mappo when they introduced their single practice for enlightenment.
ENLIGHTENMENT IN THE FINAL AGE
Keywords: Honen; Shinran; Nichiren; Buddhism; Enlightenment; mappo